Determinants of city growth in Colombia1. (March 2016) - Duranton, Gilles; Meijers, Evert; Burger, Martijn
Abstract: I develop a systematic approach to examine the drivers of population growth in Colombian cities between 1993 and 2010. Fertility plays an important role. Much of the higher growth of some Colombian cities can also be associated with higher wages. In turn, this wage advantage of some cities can be, in part, traced back to city education and industry shocks. I also find that roads and connectivity matter but obtained mixed evidence about the role of urban amenities and no evidence regarding measures of urban costs and other drivers of urban growth that have been commonly considered by past literature. I also explore some determinants of long‐run city growth going back as far as 1843.